La légende du Juif errant dans La Mémoire d’Abraham de Marek Halter - Kamiński, Paweł (Quêtes littéraires, 2014)
In the very beginning of the 17th century appears a famous legend of the Wandering Jew named Ahasverus, who is characterised by some immutable features. Since then, the story has inspired various artists and despite the passage of time it keeps on arousing a great interest among both writers and readers. The main goal of the present study is to compare the collective protagonist from The Book of Abraham, a twentieth century novel by Marek Halter, to the legendary figure. Therefore, we present a vast and accurate picture of the interactions between the Jewish protagonists from Halter’s novel to the features typical of Ahasuerus.